Law without tears. Diane Kirkby (ed), Sex power and justice: historical perspectives on law in Australia - M. San Roque (Law Text Culture, 1997)
In the introduction to this collection of 17 essays, Diane Kirkby describes her scepticism about the law's potential as a mechanism for social change. Like Carol Smart warning us of the seductive power of law (Smart 1989:160) Kirkby describes her ambivalence about a reliance on law's power to right wrongs and bring about justice. But she sees the essays in this collection as sharing a commitment to social justice and expresses a hope that the collection may itself provide an impetus for change. By situating legal practice in its social and historical contexts these contributions to the historiography of law may be capable of subverting law's claims to universality and timeless validity. Kirkby sees the book as providing a resource for the new, broadened legal education in Australia and at the very least the essays, divided into the catch-all themes of Sexuality, Punishment, Family and Citizenship and the State, provide the reader with a starting point for further research or a useful overview of areas of law and legal history in Australia. The chapters that perhaps go further than this are those that articulate more clearly Kirkby's disquiet. These are the chapters that describe the uneasy alliances between feminists and moral campaigners, the difficulty feminist activists have had in dealing with the implications of intersectional identity, the inability of (legislative) reform to provide benefits for all women and the sometimes unexpected results of feminist campaigns for change.